Digital video interventions and mental health literacy among young people: a scoping review. (2nd November 2022) - Ito-Jaeger, Sachiyo; Perez Vallejos, Elvira; Curran, Thomas; Spors, Velvet; Long, Yunfei; Liguori, Antonia; Warwick, Melaneia; Wilson, Michael; Crawford, Paul
Abstract: Background: Mental health literacy is important as it relates to understanding mental illness, increasing help-seeking efficacy, and reducing mental illness-related stigma. One method to improve the mental health literacy of young people is a digital video intervention. Aims: A scoping review was conducted to map existing research in the area of digital video interventions for mental health literacy among young people. Methods: The scoping review was conducted following the PRISMA-ScR checklist. All results were screened based on our inclusion criteria. Results: Seventeen studies were selected for analysis. In most studies ( n = 14), a digital video was the only intervention whereas three studies took a multi-intervention approach. Only two of the digital video interventions were co-created with people with mental illness or university students. All studies showed positive results in favor of digital video interventions in at least one component of mental health literacy or compared to one of the comparison conditions. Conclusions: Digital video interventions represent effective tools for enhancing mental health literacy. However, there is a need for active involvement of end-users in co-creation and to attend to the production quality so that the digital video intervention is as relevant, informed, and effective as possible.